Luxury perfusion: A paradoxical finding and pitfall of CT perfusion in subacute infarction of brain - Sotoudeh, Houman (Radiol Case Rep, 2018)
In the context of recent guidelines for stroke management, application of computed tomographic perfusion (CTP) is anticipated to increase, especially within 6-24 hours after stroke onset. There are commercially available software packages to help to detect the infarct core and the penumbra, however, the results of these software are not always straightforward that might cause incorrect CTP interpretation. We present here a case of acute ischemic stroke in which the CTP software misinterpreted the results by labeling the normal hemisphere as infarction and ischemia due to luxury perfusion of the infarcted hemisphere. Awareness of laterality of the patient's symptoms and the understanding of functioning of perfusion analysis software is necessary to avoid this pitfall.